Analysis on caprock and aquifer properties related with leakage during CO2 storage. Issue 4 (3rd July 2016) - Park, Jooseon; Park, Sung Soo; Cho, Jinhyung; Lee, Kun Sang
Abstract: One of the essential concerns in CO2 storage is the risk of CO2 leakage from the storage site. The characterization of the properties of the caprock and aquifers influencing the leakage of CO2 from storage sites into overlying formations is of significant importance. Considering solubility trapping and residual gas trapping mechanisms, numerical simulations were conducted to evaluate and understand the effects of the properties of the storage formations associated with leakage through the caprock. Based on the results, a sensitivity analysis was carried out under a wide range of variation in these properties. The formation properties included permeability and porosity of caprock and aquifer, formation dip, vertical-to-horizontal permeability ratio, salinity, and temperature. According to the simulation results, the amount of leakage increased with an increase in the permeability of the caprock and aquifer, the vertical-to-horizontal permeability ratio, and the temperature. The amount of leakage decreased with an increase in the dip angle and aquifer porosity. The sensitivity analysis indicated that the permeability of caprock, the vertical to horizontal permeability, and the dip angle had the greatest effect on the CO2 leakage. They also influenced the effects of the other properties on storage security.